Increase of Antibacterial Therapy Efficacy in Chronic Sepsis with Cycloferon and Reamberin Combination - V. M. Frolov; N. A. Peresadin; R. B. Chkhetiany; O. V. Kruglova (Антибиотики и Химиотерапия)
The use of reamberin and cycloferon combination for increasing the antibacterial therapy efficacy in patients with chronic sepsis (CS) was studied. It was shown that the combination provided more rapid elimination of the CS exacerbation symptoms, normalization of the hematologic indices, bacteriemia eradication and reduction of the cytokine blood profile - normal serum levels of proinflammatory (IL-13, IL-2, IL-6 and TNF-α) and antiinflammatory (IL-4) cytokines. The findings allowed to considered the use of the reamberin and cycloferon combination in the treatment of patients with CS pathogenetically reasonable and clinically perspective for increasing the antibacterial therapy efficacy.